2019
DOI: 10.3390/molecules24213963
|View full text |Cite
|
Sign up to set email alerts
|

Annona coriacea Mart. Fractions Promote Cell Cycle Arrest and Inhibit Autophagic Flux in Human Cervical Cancer Cell Lines

Abstract: Plant-based compounds are an option to explore and perhaps overcome the limitations of current antitumor treatments. Annona coriacea Mart. is a plant with a broad spectrum of biological activities, but its antitumor activity is still unclear. The purpose of our study was to determine the effects of A. coriacea fractions on a panel of cervical cancer cell lines and a normal keratinocyte cell line. The antitumor effect was investigated in vitro by viability assays, cell cycle, apoptosis, migration, and invasion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Gomes et al 2019 reported, leaves extract of Annona coriacea has been found to contain palmitic acid, oleic acid, asitrocinone, annonacin, trilobalicin, annomuricin E, asimicin, bullatacin, annohexocin, murihexocin, goniotriocin, bullatalicinone, annoglaucin, ginsenoside Rh5, salzmanolin, annoheptocin A, annoheptocin B, squamocin glycosylated using analysis of the electrospray ionization Fourier transform ion cyclotron resonance mass spectrometry [40].…”
Section: Annona Coriaceamentioning
confidence: 99%
“…Gomes et al 2019 reported, leaves extract of Annona coriacea has been found to contain palmitic acid, oleic acid, asitrocinone, annonacin, trilobalicin, annomuricin E, asimicin, bullatacin, annohexocin, murihexocin, goniotriocin, bullatalicinone, annoglaucin, ginsenoside Rh5, salzmanolin, annoheptocin A, annoheptocin B, squamocin glycosylated using analysis of the electrospray ionization Fourier transform ion cyclotron resonance mass spectrometry [40].…”
Section: Annona Coriaceamentioning
confidence: 99%
“…Among Annona species, in vitro antitumor potential has been demonstrated for many compounds isolated from the essential oils of leaves of A. vepretorum and A. sylvatica [ 28 ]. Different parts of A. squamosa , A. muricata , A. coriacea , and A. cacans plants carry acetogenin compounds which exhibit activity against human cancer cell lines [ 29 , 30 ]. These acetogenin compounds are typically found in Annona sp.…”
Section: Discussionmentioning
confidence: 99%
“…Natural anticancer compounds with significant efficacy extracted from plants, microorganisms, and marine organisms have been used in clinical practice 6 . Many natural products have been shown to suppress tumor growth by inducing cell cycle arrest or apoptosis 7 , 8 . Endophytic fungi constitute an enormous and comparatively untapped source of biodiversity that is considered a wellspring of effective novel natural products with potential medical applications 9 .…”
Section: Introductionmentioning
confidence: 99%